Combination of asprosin and adiponectin as a novel marker for diagnosing non-alcoholic fatty liver disease. (October 2020) - Ke, Fan; Xue, Guohui; Jiang, Xueling; Li, Fangfang; Lai, Xiaoyang; Zhang, Meiying; Shen, Yunfeng; Gao, Ling
Abstract: Background and objective: Patients with non-alcoholic fatty liver disease (NAFLD) have insulin resistance and are at an increased risk of diabetes. Recent evidence suggests that asprosin–a novel hormone secreted by white adipose tissue–may play a role in the pathogenesis of insulin resistance. However, the role of asprosin in NAFLD remains unclear. This study aimed to determine whether serum asprosin level could be used as a biochemical marker for NAFLD diagnosis. Methods: Forty-three untreated NAFLD patients and 50 sex- and age-matched healthy controls were included. Circulating serum asprosin and adiponectin (another adipokine) levels were detected by ELISA. Other metabolic parameters related to NAFLD were also determined. Results: Increased circulating serum asprosin and decreased serum adiponectin levels were found in NAFLD patients unlike in healthy controls. A positive correlation was observed between asprosin and platelet counts (PLT) ( r  = 0.3653, p  = 0.015), fasting blood glucose (FBG) ( r  = 0.3592, p  = 0.017), triglyceride (TG) levels ( r  = 0.3383, p  = 0.025), serum albumin (ALB) levels ( r  = 0.3273, p  = 0.030), and insulin resistance (HOMA-IR) ( r  = 0.4799, p  = 0.001), whereas a negative correlation existed between adiponectin and TG levels in the NAFLD group. Multivariate linear regression showed that FBG and HOMA-IR were independently related to asprosin levels. Receiver operating characteristic (ROC) curves showed that asprosin AUC and adiponectin AUC were 0.735 (95% CI 0.633–0.836, P  < 0.0001) and 0.702 (95% CI 0.597–0.807, p  = 0.0007) respectively. Moreover, the combination of both biomarkers showed good sensitivity and specificity with AUC of 0.827, which was better than the single detection of asprosin or adiponectin. Conclusion: High serum asprosin and low adiponectin level might be associated with the presence of insulin resistance in NAFLD, and the combination of asprosin and adiponectin could be a novel biomarker for diagnosing NAFLD. These data needed to be confirmed and extended in further large-population, well-designed clinical studies.